2022
DOI: 10.1086/721252
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Effects of Conspecific Aggression on Oxidative Status and Telomere Length in Zebra Finches

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Interestingly, in the model that passed all four selection criteria, affiliative behavior also had a beneficial effect on lifespan independent of its effects on telomeres. Other recent work in zebra finches showed that birds who experienced the most aggression had the highest levels of oxidative damage and the shortest telomeres ( 75 ). While this study did not measure affiliative behavior, it is possible that the birds that experienced the most aggression also received the smallest level of social support.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in the model that passed all four selection criteria, affiliative behavior also had a beneficial effect on lifespan independent of its effects on telomeres. Other recent work in zebra finches showed that birds who experienced the most aggression had the highest levels of oxidative damage and the shortest telomeres ( 75 ). While this study did not measure affiliative behavior, it is possible that the birds that experienced the most aggression also received the smallest level of social support.…”
Section: Discussionmentioning
confidence: 98%
“…In our study region, mallards are subject to increased competition and aggressive behaviour due to the presence of Egyptian geese (Hohmann and Woog, 2021), which might result in increased metabolic activity and ROS generation (Quque et al, 2022). It might also be that the higher pace of life of mallards compared to Egyptian geese and mute swans determines higher baseline generation of ROS.…”
Section: Oxygen Carrying Capacity and Oxidative Statusmentioning
confidence: 94%
“…Finally, we found that mallards had higher levels of eosinophils, basophils, oxidative damage (ROMs), and activity of the antioxidant enzyme superoxide dismutase compared to Egyptian geese and mute swans. In our study region, mallards are subject to increased competition and aggressive behaviour due to the presence of Egyptian geese (Hohmann and Woog, 2021), which might result in increased metabolic activity and ROS generation (Quque et al, 2022). It might also be that the higher pace of life of mallards compared to Egyptian geese and mute swans determines higher baseline generation of ROS.…”
Section: Methodsmentioning
confidence: 99%